Optimizing performing arts innovations at the Ceprotan ceremony: An overview of the perspective of empowering rural communities in Pacitan, Indonesia - Miftakhul Khoiriah; Silvester Pamardi; Joko Aswoyo (International Journal of Visual and Performing Arts, 2022)
Artistic research on community empowerment through artistic innovation in the Ceprotan Ceremony in Sekar Village aims to explain how the steps for optimizing performing arts innovations at the Ceprotan ceremony are through village community empowerment strategies. The initial step of this artistic research was carried out by direct observation to obtain data and information regarding the myths and practices of the Ceprotan Ceremony. In addition, to obtain more in-depth data, the researcher used the participant observer strategy and, at the same time, conducted in-depth interviews. The results of this investigation are then used by researchers to develop a community empowerment-based artistic innovation model. The results of this community empowerment-based artistic research are (1) systematic performance management; (2) the creation of social cohesion in the series of Ceprotan performances; (3) the identity of the village of Sekar is formed; (4) the revitalization of the Sekar Taji dance drama; (5) the reduction of bad events or trance (possession). The contribution of this research is an example for other regions that want to use artistic innovation as the formation of village identity and, at the same time, as an effort to complement and advance the cultural potential of Sekar Village